Pengaruh Tingkat Penghasilan, Sanksi Denda, NJOP Dan SPPT Terhadap Kepatuhan Wajib Pajak Bumi Dan Bangunan - Sri Lestari Yuli Prastyatini; Adia Adi Prabowo; Rizza Abdilanisa (Journal of Economic, Bussines and Accounting (COSTING), 2023)
This study's objective was to investigate the nature of the connection that exists between taxpayer compliance with land and building taxes and demographic factors such income, monetary penalties, NJOP, and SPPT. The sole kind of data that was employed in this investigation was primary data. The population included in this survey is comprised of Candirejo Village inhabitants who have paid land and building taxes. 120 people who lived in Candirejo Village and were obligated to pay land and building taxes made up the population. The procedure known as snowball sampling is used to choose samples. In order to examine the data, multiple linear regression is used. Both income and taxpayer compliance were determined to have a significant value of 0.836, and this value was observed for land and buildings. So, taking into consideration the t values of 2.899, 2.696, and 2.977 respectively, it is possible that NJOP and SPPT have a positive impact on taxpayer compliance with land and building taxes by way of the variable fine sanctions. Keywords: Income Level, Fine Sanctions, NJOP, SPPT, Land and Building Taxpayer Compliance.